Effect of copaiba essential oil on broiler chickens’ performance - doi: 10.4025/actascianimsci.v35i2.15376 - Aguilar, Cesar Augusto Lopez; Lima, Kedson Raul de Souza; Manno, Maria Cristina; Tavares, Fernando Barbosa; Souza, Vanessa Pereira de; Fernandes Neto, Dario Lisboa (Acta Scientiarum. Animal Sciences, 2012)
The effects of copaiba essential oil on growth performance and yield of slaughtered broilers were evaluated. Four hundred and fifty broiler chicks were distributed in a completely randomized design, with five treatments, and six replicates of 15 broiler chicks. Treatments comprised Control (commercial promoter) and four levels of copaiba essential oil, or rather, 0.15 (0.15EO); 0.30 (0.30EO); 0.45 (0.45EO) and 0.60 mL (0.60EO) kg-1 feed. The 21-day-old broilers fed on growth promoter had a greater body weight than that of birds fed on treatments with inclusion 0.30, 0.45 and 0.60 mL of essential oil (p < 0.05). Aged 40 days, only the broilers fed on treatment with high level of inclusion of essential oil showed lower body weight when compared with those fed on treatment with growth promoter (p < 0.05). Feed intake, feed conversion, viability of broilers, carcass yield, commercial cuts and weight of the internal organs were not affected by treatments (p > 0.05). The efficiency of productive index decreases in proportion to the increase of copaiba essential oil inclusion level. Copaiba essential oil may be included in the diet up to 0.15 mL kg-1 level without affecting the performance of broiler chickens.